On some problems with nonlocal integral condition - Sergejeva, Natalija (Mathematical Modelling and Analysis, 2010)
We study the second order nonlinear boundary value problems with non‐local integral conditions and construct the Fučík type spectrum for these problems.First published online: 09 Jun 2011